2023
DOI: 10.1002/smll.202206415
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Cobalt Nanodots Initiate Ferroptosis by Upregulating Heme Oxygenase 1 for Radiotherapy Sensitization

Abstract: High cobalt (Co) levels in tumors are associated with good clinical prognosis. An anticancer regimen that increases intratumoral Co through targeted nanomaterial delivery is proposed in this study. Bovine serum albumin and cobalt dichloride are applied to prepare cobaltous oxide nanodots using a facile biomineralization strategy. After iRGD peptide conjugation, the nanodots are loaded into dendritic mesoporous silica nanoparticles, generating a biocompatible product iCoDMSN. This nanocomposite accumulates in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Moreover, the additional 808 nm radiation greatly improved the generation of ROS from AH@MBTF+L group owing to the more active Fenton reaction promoted by rising temperature. In addition, the intracellular •OH level was further detected by using the specific •OH-sensitive probe (BBoxiProbe®O26) [ [45] , [46] , [47] ]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the additional 808 nm radiation greatly improved the generation of ROS from AH@MBTF+L group owing to the more active Fenton reaction promoted by rising temperature. In addition, the intracellular •OH level was further detected by using the specific •OH-sensitive probe (BBoxiProbe®O26) [ [45] , [46] , [47] ]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FTH1 is a key iron storage protein whose light and heavy chains and Solute Carrier Family 40 Member 1 (SLC40A1) are controlled by Nrf2. and In addition, Nrf2 upregulates the expression level of heme oxygenase 1 (HO-1) [35]. The study demonstrated that inhibition of the PERK/Nrf2 pathway ameliorated resistance to G9a inhibition in leukemia cells and increased ROS and down-regulated HO-1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Fenton reaction, GSH depletion, GPX4 suppression, NOXs activation, and DNA damage 4T1 cells [194] Ferroptosis PDT GOX mimicking activity, GSH depletion, and Fenton-like reaction 4T1 cells [198] iCoDMSN Co 2+ and ionizing radiation Fenton-like reaction, KEAP1 downregulation, NRF2 and HMOX1 upregulation, Fe 2+ accumulation 4T1 cells [199] BSO/ZIF8@Au@MPN@HA BSO, Au NPs, and Fe 3+ , X-ray GSH depletion, GPX4 inactivation, and Fenton reaction 4T1 cells [200] Ferroptosis Microwave therapy ADM/Fe instability of Cu + . Consequently, this has prompted researchers to explore innovative strategies to deliver Cu 2+ and subsequently convert it to Cu + within tumor cells, thereby facilitating the induction of cuproptosis.…”
Section: Synergistic Therapy For Boosting Ferroptosis-based Cancer Th...mentioning
confidence: 99%